A CASE REPORT OF MESENTERIC LIPOMA GROWING SUBPEDICULATELY - OONO, Kouichi; KATOH, Hiroyuki; TAKEMOTO, Norihiro; SEKISHITA, Yoshiaki; FUJIMORI, Masaru; SHIONO, Tsuneo (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
A 70-year-old woman was admitted to the hospital because of nausea and vomiting. Ultrasound revealed a hyper echoic mass 10cm in diameter in the lower abdomen. Computed tomographic and magnetic resonance imaging scans showed same density and intensity mass as fatty tissue, which had a septum. The preoperative diagnosis was lipoma in the abdomen. At laparotomy, a large tumor 10cm in diameter was found growing subpediculately from the small bowel mesentery. The tumor was resected with a partial resection of the ileum. The resected material disclosed a yellow and elastic soft tumor with the dimension of 14×12×5cm and the weight of 450g. Neither hemorrhage nor necrosis was detected. The histological diagnosis was lipoma arising from the small bowel mesentery. Mesenteric lipomas are rare among tumors arising from the mesentery, especially the lipomas growing with pedicle. So far a few cases of subpediculate mesenteric lipoma have been reported.